Anatomic Considerations for Injection of the Lateral Atlanto-Axial Joint. Issue 11 (1st July 2019) - McNabney, Charis; Chavda, Anesh; Alabsi, Hatim; Sellers, Stephanie L; Murphy, Darra T; Fenton, David
Abstract: Objective: We aimed to define the potential complications of intra-articular steroid injections into the lateral C1-2 articulations and safety margins to the relevant structures. Methods: A total of 488 contrast-enhanced computed tomography angiogram (CTA) "arch to vertex" studies were retrospectively reviewed for theoretical intersection of the vertebral artery or thecal sac and distance of the named structures from the anticipated/theoretical trajectory of injection into the lateral C1-C2 joint. Results: Patients were 60.4±15.8 years old and 55.5% male. In total, seven vertebral arteries and 11 thecal sac theoretical intersections were found. In cases without a direct intersection, the distance from the trajectory (range) was 0.71±0.18 (0.22–1.44) cm to the vertebral artery and 0.6±0.22 (0.14–1.8) cm to the thecal sac. Conclusions: Although injection of steroid into the lateral C1-C2 articulation for pain management has historically been reported to carry risk of severe complications due to close proximity and location variability of surrounding structures, our study quantifies the potential risk of such injections. Further, our analysis suggests that preprocedural imaging should be considered.